Avaliação da qualidade da água da bacia hidrográfica do rio Sergipe usando análises multivariadas de dados - Silveira, Alzenia Menezes (2014)
This paper was aimed to asses and expounds the physical, chemical and microbiologic parameters which interfere in the quality of water of Sergipe River watershed. It was done from the information taken out from a research report done by FAPITEC/SE/MCT/CNPq/2007; to asses metals and trace-elements in the watershed of Japaratuba River, Sergipe River, Vaza-Barris River, Piaui River and Real River in Sergipe State, it was detailed by Researcher Doctor Professor Maria Nogueira Marques and the team of Instituto de Pesquisa Tecnologico de Sergipe – ITPS; to verify the quality of the water in those watershed, based on Water Quality Index (WQI). It was done an analysis of the data collected in this research. It was also done a multivariate data analyzed as well as main components – PCA and analysis of hierarchic group – HCA, the collected sample was analyzed based on physical, chemical and microbiologic parameters of DBO, turbidity, apparent color, pH, OD, chlorophyll-a, total dissolvent solid, oil and waxes, total phosphor, ammoniac nitrogen, CI, NO2, NO3, SO4-2, PO4-3, NA+, K+, Mg2+, Ca2+, CI, SO42-Cu, Mn, Ph, Cr, Ni, Cd, Pb, Zn, COT and thermotolerant coliform. The samples were collected in six parts of sample Sergipe River watershed in the period of dry and rainy and the samples were analyzed by the standard methods to analyze water and effluents the ―Standard Methods for the Examination of Water and Wastewater‖ (2005) – SMEWW and U.S. Environmental Protection Agency – Method 300.0 – US-EPA 300. The results present high value of concentration for turbidity, apparent color, pH, dissolved oxygen, conductibility, total hardness, oil and waxes, total alkalinity and total dissolved solid; great ions: Na+, K+, Mg2+, Ca2+, CI, SO42-, chlorophyll-a and nutrients; total phosphor, total nitrogen: N-NH3, NO3-, NO2-, PO43-, TOC, DBO, DQO, coliform and Ph, all of them over the maximum value allowed by the resolution nº 357/2005 from Conselho Nacional de Meio Ambiente – CONAMA for rivers type 1 and 2, which classify the water destined for human consume. With the results collected after adding of analysis PCA and HCA, it was identified that tendency of possible groups with point P1 and P5 and the parts P3 and P4 for every parameters analyzed altogether. Even analyzing the parameters according to matrix of correlation, it is possible to observe tha the same points self-separated indicating in the results the contamination which occur in the area of Sergipe River watershed, for anthropogenic actions due to the use and occupation of the ground, indicating the necessity of developing actions to control and tentative of shorten the impact generated because of those actors of pollution.